Intelligent routing and scheduling strategies for heterogeneous instant delivery services: Optimizing efficiency, customer satisfaction, and sustainability - Guo Wang Hou; Cen Zhou Fang (International Journal of Enterprise Modelling, 2022)
Intelligent routing and scheduling strategies play a crucial role in optimizing efficiency, customer satisfaction, and sustainability in heterogeneous instant delivery services. This research focuses on developing a mathematical formulation and algorithm to address these challenges. The proposed model considers various factors, including delivery orders, vehicle capacities, time windows, and environmental impact, to minimize cost, delivery time, and emissions. The research also explores the integration of multi-objective optimization techniques to strike a balance between conflicting objectives. A numerical example is presented to illustrate the application of the mathematical formulation, showcasing the benefits of the proposed strategies in terms of efficient vehicle assignment, timely deliveries, and reduced environmental footprint. The findings highlight the potential for improving instant delivery services through intelligent routing and scheduling strategies, leading to enhanced operational efficiency, customer satisfaction, and sustainability. Further research is recommended to validate the proposed strategies in real-world scenarios and explore additional factors that may impact the routing and scheduling process in heterogeneous instant delivery services